Neurologic melioidosis presented as encephalomyelitis and subdural collection in two male labourers in India - Kavitha Saravu; Rajagopal Kadavigere; Ananthakrishna Barkur Shastry; Rohit Pai; Chiranjay Mukhopadhyay (Journal of Infection in Developing Countries)
Two distinct and potentially deceitful cases of neurologic melioidosis are reported. Case 1: A 39-year-old alcoholic and uncontrolled diabetic male presented with cough, fever, and left focal seizures with secondary generalization. An magnetic resonance imaging (MRI) brain scan revealed a small peripherally enhancing subdural collection along the interhemispheric fissure suggestive of minimal subdural empyema. Blood culture grew Burkholderia pseudomallei. Patient was diagnosed with disseminated bacteraemic melioidosis with subdural empyema. He was successfully treated with ceftazidime-cotrimoxazole-doxycycline. Case 2: A 45-year-old male presented with left lower limb weakness, difficulty in passing urine and stool, and back pain radiating to lower limbs. Neurological examination revealed flaccid left lower limb with absent deep tendon reflexes and plantar reflex. Spinal MRI showed T2 hyperintensity from D9 to L1 suggestive of demyelination. Patient was treated with high dose methylprednisolone. By day 3 of steroid treatment, lower limb weakness progressed. Subsequent MRI showed extensive cord hyperintensity on T2 weighted sequence extending from C5 to conus medullaris consistent with demyelination. Cerebrospinal fluid (CSF) culture grew B. pseudomallei, and the patient was given meropenem-cotrimoxazole. After three weeks of parenteral treatment, the lower limbs remained paralyzed. Patient was discharged on oral cotrimoxazole-doxycycline. Conclusions: Melioidosis should be considered as a differential in focal suppurative central nervous system (CNS) lesions, meningoencephalitis, or encephalomyelitis in endemic areas. CNS infections must be ruled out prior to steroid administration. The role of corticosteroids in demyelinating CNS melioidosis has been refuted. This is a rare documentation of effect of unintentional corticosteroid treatment in melioidosis.